The Implementation of Al-Islam Kemuhammadiyahan Character Education in Muhammadiyah Charity Business: Implementasi Pendidikan Karakter Al-Islam Kemuhammadiyahan di Amal Usaha Muhammadiyah - Wakit , Saipul; Rusdiyanto, Rusdiyanto; Rais, Rinovian; Kamaruddin, Ilham; Dacholfany, Muhammad Ihsan (Halaqa: Islamic Education Journal, 2023)
Implementation of character education is an effort to increase knowledge and familiarize good behavior for students. The main characters are the values of the Islamic religion and Muhammadiyah which are the basis of life. The characteristics of al-Islam Muhammadiyah include good morals, faith, piety, honesty, discipline and firmness in Muhammadiyah organization. Practically the purpose of this study is to find out how the efforts made by Muhammadiyah educational institutions at the secondary level in increasing knowledge, habituation and the implications of implementing character education. The research method used in this research is a qualitative method with a case study approach. As for data collection techniques through observation, interviews and documentation related to Islamic character. The results of the research are 1) increasing knowledge of Al-Islam Muhammadiyah character education through classroom learning and training. 2) the implementation of the habituation of the Muhammadiyah Al-Islam character is carried out through carrying out mandatory worship, sunnah, praying, reading the Koran, morals and social activities. 3) the implementation of Al-Islam Muhammadiyah character education has implications for increasing knowledge, forming the habit of carrying out amaliyah according to true Islamic teachings, and having knowledge and experience in the Muhammadiyah organization by actively participating in Muhammadiyah activities in schools and the community.